2015
DOI: 10.15344/2394-1502/2015/108
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antioxidant Effect of the Leaf and Branch Extracts of Ribes L. Species in Turkey

Abstract: Background: There are most studies on the antioxidant activity of Ribes nigrum and R. rubrum; however, this activity has been restricted on the other species. In the present study, the phenolic contents and antioxidant activities of different extracts prepared with methanol (MeOH), dichloromethane (DCM), ethyl acetate (EtOAc), n-buthanol (BuOH) and water from the leaf and branch of Ribes alpinum,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Blackcurrant leaves collected in 2019 showed the highest content of polyphenols regardless of harvest time (Table 2). Our findings are in line with data published by Kendir and Köro glu [30]. These authors also showed a higher polyphenol content in blackcurrant leaves (26,000 mg/100 g DM) than in redcurrant leaves (18,031 mg/100 g DM).…”
Section: Total Phenolic Content and Antioxidant Activitysupporting
confidence: 93%
See 2 more Smart Citations
“…Blackcurrant leaves collected in 2019 showed the highest content of polyphenols regardless of harvest time (Table 2). Our findings are in line with data published by Kendir and Köro glu [30]. These authors also showed a higher polyphenol content in blackcurrant leaves (26,000 mg/100 g DM) than in redcurrant leaves (18,031 mg/100 g DM).…”
Section: Total Phenolic Content and Antioxidant Activitysupporting
confidence: 93%
“…This could be due to differences in extraction times. There were significant differences between time of extraction in the preparation of our samples (2 h) and extraction of up to 8 h by Kendir and Köroglu [30]. As pointed out by Zych et al [40] extending the extraction time increases the antioxidant activity against the DPPH free radicals in redcurrant leaves but decreases in blackcurrant leaf extracts.…”
Section: Total Phenolic Content and Antioxidant Activitymentioning
confidence: 71%
See 1 more Smart Citation
“…Suzutani et al, 15 noted that phenolic compounds (such as anthocyanins) found in the extracts of Ribes species may be a key factor in the antiherpesvirus activity of these extracts. The total phenolic contents of methanol and aqueous extracts prepared from the leaves of R. uva-crispa were 273.13, 341.25 mg/g, respectively, while total phenolic contents of the methanol and aqueous extracts prepared from the leaves of R. multiflorum were 368.44, 490.63 mg/g, respectively from a study 29 .…”
Section: Resultsmentioning
confidence: 91%
“…belong to the Grossulariaceae. Currants and gooseberries are deciduous evergreen shrubs (Kendir and Koroglu, 2015) which are found in the cold and temperate regions of North America, Europe, Asia, and South America (Pfister and Sloan, 2008). Red currant (Ribes rubrum L.), black currant (Ribes nigrum L.), rock currant (Ribes petraeum L.), mountain currant (Ribes alpinum L.), and oriental gooseberry (Ribes orientale L.) are all found in the flora of Turkey (Ercisli, 2004).…”
Section: Vaccinium Spp: Caucasian Whortleberry (Vaccinium Arctostaphy...mentioning
confidence: 99%